Membrane actions of RC slabs in mitigating progressive collapse of building structures - Tan, Kang Hai (2011)
The potential for progressive collapse of RC buildings can be studied using column loss scenarios. The loss of either internal or external penultimate columns is among the most critical scenarios since the affected beam-and-slab substructure associated with the removed column becomes laterally unrestrained with two discontinuous slab edges. At large deformations, the membrane behaviour of the affected slab, consisting of a compressive ring of concrete around its perimeter and tensile membrane action in the central region, represents an important line of defense against progressive collapse. The reserve capacity can be used to sustain the amplified gravity loads and to mitigate the progressive collapse of building structures. In this paper, an advanced finite model (FEM), which is first verified by available test data, is used to investigate the membrane behavior of RC slabs under the effect of three conditions: The presence of interior beams, rotational restraint along the perimeter edges of the slabs and top reinforcement. It is found that with the presence of interior beams, more tensile membrane forces may be mobilized in the central region as the beam reinforcement is in tension together with slab reinforcement. In the outer region, the compressive ring of concrete which equilibrates the tensile membrane forces may also be strengthened by hogging moment in the top reinforcement along the perimeter edges. These conditions actually enhance the load-carrying capacity of the beam-slab structure to sustain the applied load severely amplified by the doubling-of-span effect due to the loss of a supporting column.